Regulating Content on The Internet - The Way Forward: A Discussion - Nehaluddin AHMAD; Abdul Mohaimin AYUS; Sulaiman DORLOH (Communications of International Proceedings, 2022)
Online freedoms are seen as inseparable parts of liberal democracies. In the contemporary world, not only in India or US but in many other countries, there are many people who use social media platforms and digital news outlets as analternative to traditional media which consists of TV channels, radio, and print media. In such an environment, online freedoms are significant to be able to reach information. This paper will examine the concept of online hate speech and highlight the specific issues connected to it. The paper describes international, regional, and national approaches to Internet censorship regulation, compares legislations of different countries, bringing out the problems caused by clashes in national laws, and finally reviews different mechanisms for combating such issues and attempts to answer how could it be balanced.
Keywords: Censorship; Pornography; Privacy Protection; Cyber-homophobia